Chronic Obstructive Pulmonary Disease Illness and Medication Beliefs are Associated with Medication Adherence. (14th April 2015) - Krauskopf, Katherine; Federman, Alex D.; Kale, Minal S.; Sigel, Keith M.; Martynenko, Melissa; O'Conor, Rachel; Wolf, Michael S.; Leventhal, Howard; Wisnivesky, Juan P.
Abstract Almost half of patients with COPD do not adhere to their medications. Illness and medication beliefs are important determinants of adherence in other chronic diseases. Using the framework of the Common Sense Model of Self-Regulation (CSM), we determined associations between potentially modifiable beliefs and adherence to COPD medications in a cohort of English- and Spanish-speaking adults with COPD from New York and Chicago. Medication adherence was assessed using the Medication Adherence Report Scale. Illness and medication beliefs along CSM domains were evaluated using the Brief Illness Perception Questionnaire (B-IPQ) and the Beliefs about Medications Questionnaire (BMQ). Unadjusted analysis (with Cohen's d effect sizes) and multiple logistic regression were used to assess the relationship between illness and medication beliefs with adherence. The study included 188 participants (47% Black, 13% Hispanics); 109 (58%) were non-adherent. Non-adherent participants were younger (p < 0.001), more likely to be Black or Hispanic (p = 0.001), to have reported low income (p = 0.02), and had fewer years of formal education (p = 0.002). In unadjusted comparisons, non-adherent participants reported being more concerned about their COPD (p = 0.011; Cohen's d = 0.43), more emotionally affected by the disease (p = 0.001; Cohen's d = 0.54), and had greater concerns about COPD medications (p < 0.001, Cohen's d = 0.81). In adjusted analyses, concerns about COPD medications independently predicted non-adherence (odds ratio: 0.52, 95% confidence interval: 0.36–0.75). In this cohort of urban minority adults, concerns about medications were associated with non-adherence. Future work should explore interventions to influence patient adherence by addressing concerns about the safety profile and long-term effects of COPD medications.